PROJECT METHOD OF TRAINING FUTURE MATHEMATICS TEACHERS (International conference on multidisciplinary science, 2025)
The article examines the issue of implementing the project method in mathematical and methodological disciplines, and provides an example of a series of projects implemented in the course of mathematical analysis and methods of teaching mathematics. A description of some specific projects is also included. The role of project-based learning in training mathematics teachers is discussed.